Towards value from waste: Bioreactor selection for the reduction of nutrient load and production of Poly-y-glutamic acid - Raper, Tayana (Department of Chemical Engineering, 2023)
Humanity is reaching a critical point in history where the re-use of resources previously classified as waste is becoming a necessary strategy to long term sustainability, through concepts such as circular economies. The re-use and reimagination of wastewater through the concept of a wastewater biorefinery (WWBR) is one such potential opportunity. It is the merging of integrated wastewater processing with bioproduction of valuable products from a waste stream, whilst still achieving clean water as an equally important and valuable product. These value-add products need to have sufficient value, and fulfil a market need to ensure that the WWBR is economically viable. South Africa's wastewater treatment plants, whilst faced with the challenges of rapidly growing populations, limited financial investment in infrastructure, maintenance and skilled operators, have the potential to achieve the goals of the bioeconomy and wastewater treatment through the implementation of the wastewater biorefinery concept. One of the main challenges facing the implementation of WWBR is the dilute and non-sterile nature of the wastewater. In traditional bioprocessing, this does not favour product formation due to the high flowrate and dilute streams. However, through optimisation of bioreactor design and careful selection against a set of design and operational criteria, a suitable reactor technology can be chosen that will facilitate bioproduction from these dilute streams and overcome the tensions. This project investigated the current wastewater treatment technologies used in a South African context and selected a reactor technology that meets the bioreactor selection criteria to address the challenges of bioproduction. To test its concept, the study focuses on an example product and microorganism from wastewater. One such product that has high potential for application in a WWBR is poly-ɣ-glutamic acid (ɣ-PGA.) It is a naturally occurring biopolymer with potential for application in medical, food, agricultural, wastewater treatment and cosmetic industries. A known ɣ-PGA-producing Bacillus subtilis strain was isolated (referred to as Isolate 1) from a wastewater treatment facility in Mitchells Plain, South Africa by Madonsela (2013). The kinetics of Isolate 1 were studied in stirred tank reactors (STRs) with a dilute minimal media under ideal temperature conditions (37°C) as well as uncontrolled room temperature to mimic environmental fluctuations that could be seen in a WWBR. The biomass productivity and maximum specific growth rates were estimated. Fed-batch room temperature cultivation was used to investigate if the biomass and PGA productivities could be maintained over extended time by feeding at the maximum glucoseutilisation rate seen during the batch cultivations. The maximum specific growth rates determined were used to inform the critical dilution rate expected in the continuous experiments. A detailed review of the existing reactor technologies used in South Africa's wastewater treatment plants was contrasted against the criteria for WWBR reactor selection, and through further literature review and refinement of the criteria, a SWOT analysis was done. The Moving Bed Biofilm Reactor or MBBR fulfilled the key criteria of a WWBR. With its reputation as a simple, yet robust technology with the ability to be retrofitted into existing wastewater treatment plant infrastructure (Odegaard, 2006; Wang et al., 2006; van Haandel & van der Lubbe, 2012), it was identified as the most promising reactor technology to investigate the aims of this research. A lab-scale MBBR was designed and constructed to demonstrate the continuous production of ɣ-PGA and the impact of biomass retention on productivities and nutrient removal, under continuous and nonsterile conditions. The dilution rate was increased beyond the calculated critical dilution rate to confirm that biomass retention would allow operation at higher dilution rates, whilst still maintaining or improving biomass and ɣ-PGA yields. The results from the STR batch cultivations compared the growth and productivity of Isolate 1 (Bacillus subtillis) at room temperature (RT) and 37 °C. The overall and maximum biomass productivities in the room temperature batch cultivations were an average of 0.071 ± 0.007 g/L/h and 0.425 ± 0.108 g/L/h respectively. These increased to 0.174 g/L/h and 1.246 g/L/h at 37 °C. The maximum specific growth rates under the RT conditions achieved average values of 0.150 ± 0.049 h -1 and 0.376 h -1 at 37 °C. Based on the maximum specific growth rates, a range of critical dilution rates were calculated to guide the process design and operating parameters in the continuous cultivation studies. Duplicate fed-batch experiments were conducted with the feed-rate set to the maximum glucose utilisation rate calculated from the batch experiments to achieve a final glucose loading of 2.86 g/L/h. Overall biomass productivities were increased from batch to fed batch phase from 0.092 ± 0.004 g/L/h to 0.189 ± 0.008 g/L/h. The average overall yield and productivities of ɣ-PGA (YP/S) in the fed-batch cultivations were calculated to be 0.681 ± 0.066 gP/gS and 0.667 ± 0.801 g/L/h. Following the design and construction of the MBBR, optimal operating parameters such as the loading of carrier and aeration rate needed to be found. Mass transfer studies using the static gassing in-out method were conducted to determine the preferred biofilm carrier loading (percentage of carrier volume in the reactor working volume) allowing the highest oxygen mass transfer. It was found that the optimal filling percentage was 40% and aeration rates of 3 to 5 L/min with volumetric mass transfer coefficient range of 17.23 to 35.64 h -1 . Hydrodynamic studies conducted at three different retention times (24h, 12 and 6 hours) and fixed aeration rate of 4 L/min. An increase in the liquid flowrate through the reactor resulted in shortened mixing times. No dead zones were observed. The mixing times of 40.5 ± 5.2 minutes (24 h), 24.5 ± 3.8 minutes (12 h) and 12.5 ± 2.7 minutes (6 h) found to be significantly smaller than the retention times, and thus the system was well-mixed with no visible dead zones or poor mixing. Biofilm attachment of Isolate 1 was demonstrated on the K3 Annox Kaldnes9® carriers. After a 4-week acclimation period, SEM imaging confirmed a thin and robust biofilm layer consisting of rod-shaped Bacillus-looking cells on the carriers. The MBBR continuous studies were commenced at a 24 h retention time (0.042 h-1 dilution rate) to ensure adequate biofilm retention and attachment onto the carriers. SEM imaging of the carriers again confirmed the presence of attached biofilm and dominance of rod-shaped bacteria as expected from Bacillus subitilis. The dilution rate was gradually increased until it reached the critical dilution rates calculated from the RT batch experiments. To test the robustness of the system the dilution rates were doubled twice thereafter until a decrease in substrate utilisation was observed at dilution rate 3-fold higher than the critical dilution rate. The retention times tested were 24, 21, 15, 10, 6.6, 4 and 2 hours (corresponding dilution rates of 0.042, 0.048, 0.037, 0.100, 0.152, 0.250 and 0.500 h-1 ). The steady-state results showed an increase in biomass and ɣ-PGA productivities with an increase in dilution rate. The biomass productivity increased from 0.156 g/L/h at 24 h (0.042 h-1 ) to 0.839 g/L/h at 2 h (0.500 h -1 ). The substrate utilisation (total carbon fed) decreased from 100% at a retention time of 0.042 to 95% at a retention time of 0.500 h-1 , while ɣ-PGA productivity increased from 0.367 g/L/h to 7.519 g/L/h. At dilution rates > 0.152 h-1 , the OD600 of the planktonic cell started to decrease. This is a significant result as, in a suspension culture, it would signify that cell washout was occurring and there would be a decrease in productivity. This is, however, not the case with productivity increasing; this demonstrates that significant biomass retention and biofilm development within in the MBBR and the uncoupling of hydraulic and biomass retention times drive productivity up, with decreasing dilution rates. One of the key objectives of this research was to demonstrate the proof of concept of the MBBR following its selection against key criteria required for the WWBR bioreactor and prove that bioproduction is possible. The MBBR was able to achieve increasing productivities of biomass and ɣPGA and high substrate utilisation at dilution rates higher than the critical dilution rate. This result demonstrates that WWBR using existing wastewater reactor technologies have great potential. Alongside this, the MBBR is easily retrofitted into existing activated sludge infrastructure that is widely used across South Africa. It is recommended that further study at a larger scale and conditions closer mimicking those of a WWTP be investigated to further test the potential of a WWBR in a South African context in fulfilling the sustainable future we all hope to achieve.